Beyond Imported Magic : Essays on Science, Technology, and Society in Latin America - Holmes, Christina, 1973-; Marques, Ivan da Costa; Medina, Eden, 1976- (Book collections on Project MUSE., 2014)
The essays in this volume study the creation, adaptation, and use of science and technology in Latin America. They challenge the view that scientific ideas and technology travel unchanged from the global North to the global South - the view of technology as 'imported magic'. They describe not only alternate pathways for innovation, invention, and discovery but also how ideas and technologies circulate in Latin American contexts and transnationally.